Pengaruh Live Streaming, Video Marketing, dan Flash Sale terhadap Keputusan Pembelian pada Pengguna Aplikasi Shopee (Studi Kasus Mahasiswa Universitas Bandar Lampung) - Harun, Renaldi; Narundana, Vonny Tiara (ARZUSIN, 2025)
This study aims to examine the influence of live streaming, video marketing, and flash sale on purchasing decisions of Shopee platform users, with research subjects being students of Universitas Bandar Lampung. Using a total sample of 98 respondents and multiple linear regression analysis, the findings reveal that live streaming and video marketing features have a significant positive impact on purchasing decisions, with coefficient values of 0.212 and 0.327, respectively. Conversely, the flash sale feature has a negative but insignificant influence, with a coefficient value of -0.028. Simultaneously, the three features contribute significantly to purchasing decisions, with an R² value of 36.6%. These results suggest that live streaming and video marketing are more effective in capturing consumer attention, while flash sales require further evaluation regarding stock limitations and time pressure. These findings have strategic implications for e-commerce platforms and sellers to optimize interactive features to enhance shopping experiences and consumer purchasing decisions.